2017
DOI: 10.1007/s10120-017-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of a combination of capecitabine, cisplatin, and intraperitoneal docetaxel (XP ID) in advanced gastric cancer patients with peritoneal metastasis

Abstract: Our study indicated that XP ID was effective, with manageable toxicities, in AGC patients with peritoneal metastasis. As the cumulative incidence of abdominal pain was probably related to bowel irritation by ID, it might be necessary to modify the dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Peritoneal metastasis (PM) is the most common mode of metastasis in gastric cancer and a critical indicator of poor prognosis [ 2 4 ]. Although various approaches to the treatment of PM have been assessed, including systemic and/or intraperitoneal chemotherapy [ 5 8 ], hyperthermic intraperitoneal chemotherapy (HIPEC) [ 9 , 10 ], and aggressive surgery (peritonectomy) [ 11 , 12 ], satisfactory outcomes have not been achieved. PM is characterized by rapid infiltration and proliferation of cancer cells accompanied by extensive stromal fibrosis, causing potentially fatal disorders such as bowel obstruction, hydronephrosis, and jaundice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal metastasis (PM) is the most common mode of metastasis in gastric cancer and a critical indicator of poor prognosis [ 2 4 ]. Although various approaches to the treatment of PM have been assessed, including systemic and/or intraperitoneal chemotherapy [ 5 8 ], hyperthermic intraperitoneal chemotherapy (HIPEC) [ 9 , 10 ], and aggressive surgery (peritonectomy) [ 11 , 12 ], satisfactory outcomes have not been achieved. PM is characterized by rapid infiltration and proliferation of cancer cells accompanied by extensive stromal fibrosis, causing potentially fatal disorders such as bowel obstruction, hydronephrosis, and jaundice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…assessed, including systemic and/or intraperitoneal chemotherapy [5][6][7][8], hyperthermic intraperitoneal chemotherapy (HIPEC) [9, 10], and aggressive surgery (peritonectomy) [11,12], satisfactory outcomes have not been achieved. PM is characterized by rapid in ltration and proliferation of cancer cells accompanied by extensive stromal brosis, causing potentially fatal disorders such as bowel obstruction, hydronephrosis, and jaundice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the optimal dose should be tested for agents used in IP chemotherapy. In determining the recommended dose (RD) of IP docetaxel, Cho et al [59] tried IP docetaxel at 3 different dose levels (100, 80, or 60 mg/m 2 ). As a result, they found that the RD of intraperitoneal docetaxel (100 mg/m 2 ) was effective with manageable toxicities in the treatment of GC patients with PM.…”
Section: Conversion Therapy Of Gastric Cancer Patients With Peritoneamentioning
confidence: 99%
“…And researchers considered that the frequent grade 3/4 abdominal pain was due to bowel irritation caused by IP chemotherapy [60]. However, it was treatable by dose reduction and the therapy of analgesics in majority of the patients, and none of them discontinued treatment due to bellyache [59].…”
Section: Conversion Therapy Of Gastric Cancer Patients With Peritoneamentioning
confidence: 99%